Conceptualising a social business blockchain: The coexistence of social and economic logics - Devine, Anthony; Jabbar, Abdul; Kimmitt, Jonathan; Apostolidis, Chrysostomos (Technological forecasting & social change, 2021)
•Social and economic logics can co-exist harmoniously when facilitated by a social blockchain.•Blockchain technology utilising smart contracts can improve the effectiveness of social businesses.•A conceptual map for the development of a social blockchain is created using Yunus’ principles.•A social blockchain leads to a shift in focus from trust in organisations to trust in technology and algorithms. In this paper we explore how blockchain and smart contracts can build trust and act as catalysts for sustainable social businesses by supporting the coexistence of social and economic logics of social ventures. To achieve this we draw upon Yunus’ seven principles of social business to present six emergent questions challenging how blockchain can improve the sustainability of social ventures and support the fulfilment of the principles. Our contribution is a social business blockchain model, codifying Yunus’ principles as smart contract functions, offering novel insights into how blockchain could be utilised to promote the coexistence of social and economic logics (i.e. the defining characteristics of a social business). In addition, it demonstrates that implementation of this technology elicits new types of trust relationships between stakeholders, social businesses and the blockchain, which can be facilitated through the use of smart contracts.